Processos de desinstitucionalização em CAPSad - Carvalho, Ariane Brum de (2010)
This paper had the objective of tracing a cartography of deinstitutionalization processes at CAPSad (Psychosocial Attention Centre) in Aracaju referring to the period I was part of the management of this service - in 2007. To reach this goal, we used field diary as field register and mnemonic register. This is a cartographic narrative, understood as a narrative which forces a detachment from what is said, to research the conditions for its production. Focused on CAPSad micropolitical sphere, we brought up concrete situations from the service‟s routine articulating it to social and historical conditions and also with the Integral Attention to Alcohol and Other Drugs Users Policy and Psychiatric Reform. This paper is not only a description of a personal management experience, it points to a collective field of management and work processes implicated with specific political policies and also the questioning and to wonder about what is already instituted. The deinstitutionalization paradigm intended by the Psychiatric Reform gather potency when linked to real and concrete problems that appear on daily practices, which solutions are built by the people who experience and legitimate these practices.